Feminisme Dalam hubungan Psikoanalisis Julia Kristeva - Firdausiyah, Umi Wasilatul (Jurnal Penelitian Humaniora, 2021)
Events relating to womanhood are never separated from their relationship with men. This paper aims to read Julia Kristeva's thoughts in seeing the intersection of her thoughts between feminism and her psychoanalysis, assisted by Library Research research and using the historical descriptive-analytical type method, as a bridge to explain Kristeva's thinking about feminism. The result of this research is the relationship between Julia Kristeva's feminism and her psychoanalytic role, making feminism a symbol or marker, and discussion of women's advocacy and struggle for patriarchal culture. In addition, according to him, feminism theory also shows the existence of humiliation which is the instability of the subject. As an international philosopher and intellectual, Kristeva rejects herself as feminism, it's just that Kristeva argues that women need to find a list of alternative psychics outside of patriarchal rules if they are to discover their own truths that can be found in semiotic motility.Keywords: Feminism, Julia Kristeva, Women, Gender, Psychoanalysis